Consumer Demand for Online Dizziness Information: If You Build it, They may Come - Kerber, Kevin A.; Skolarus, Lesli E.; Callaghan, Brian C.; Zheng, Kai; Zhang, Yuhao; An, Lawrence C.; Burke, James F. (Frontiers in Neurology, 2014)
Objective: Dizziness is a common reason patients present to doctors, but effective diagnostic tests and treatments for dizziness are underused. The internet is a way to disseminate medical information and is emerging as an intervention platform. The objective of this study was to describe internet searches for dizziness terms to assess the possible consumer demand for internet-based dizziness diagnostic and treatment tools. Study Design/Methods: Google AdWords and Google Insights for Search were used for keyword search data on the following generic terms: vertigo, dizzy, dizziness, lightheaded, and lightheadedness. Data collected included keyword ideas (i.e., additional keywords identified by Google as being related search terms), global and U.S.-only monthly search frequencies, as well as trends in top searches related to dizziness terms from 2004 to 2012. Keywords suggestive of benign paroxysmal positional vertigo (BPPV) or BPPV processes were identified. Results: Of the five generic dizziness terms, vertigo had the most global searches per month (1.83 million) and lightheadedness had the least (90,500). Four BPPV specific terms had more than 100,000 global searches per month. Three BPPV terms (“positional vertigo”, “benign vertigo”, and “benign positional vertigo”) have been in the list of top searches related to vertigo every quarter since 2004. Conclusions: Substantial demand exists for dizziness information via the internet. Future studies should seek to better characterize the population seeking this information. The magnitude of this potential demand suggests that validated and tested diagnostic and treatment tools could contribute to healthcare efficiencies and patient outcomes.